Roland Jooris : De 7. - Het Roger Raveelmuseum, Machelen-aan-de-Leie (Leuven : Cera Foundation, 2007)
Jooris, Roland ; Cortier, Amédée ; De Keyser, Raoul ; Heyvaert, René ; Mees, Guy ; Raveel, Roger ; Van Severen, Dan ; Wéry, Marthe
Roland Jooris De 7., Het Roger Raveelmuseum, Machelen-aan-de-Leie, van zondag 3 juni tot en met zondag 23 september 2007
kunstcatalogus